2016
DOI: 10.1371/journal.pone.0147693
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Tangshen Formula on Diabetic Nephropathy in Rats

Abstract: ObjectiveInflammation and fibrosis are essential promoters in the pathogenesis of diabetic nephropathy (DN) in type 2 diabetes. The present study examined the anti-inflammation and anti-fibrosis effect of Tangshen Formula (TSF), a traditional Chinese medicine, on DN.Research Design and MethodsProtective role of TSF in DN was examined in a rat model of type 2 DN that was established by high-fat diet-fed and low-dose-streptozotocin injection. TSF was suspended in 0.5% CMC-Na solution and delivered by oral gavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 33 publications
1
47
0
Order By: Relevance
“…Asperulosidic acid, a bioactive iridoid glycoside, can also exert renal protective effects by inactivating both TGF-β/Smad and NF-κB signaling pathways (Xianyuan et al, 2019). Similar therapeutic effects are also found in other studies with herbal medicines (Nie et al, 2014;Wan et al, 2014;Zhao et al, 2016). Targeting Smad3-dependent non-coding RNAs could be another therapeutic approach to treat renal fibrosis and inflammation (Figure 4c).…”
Section: Treatment Of Ckd By Targeting Downstream Tgf-β/smad Signalinsupporting
confidence: 62%
“…Asperulosidic acid, a bioactive iridoid glycoside, can also exert renal protective effects by inactivating both TGF-β/Smad and NF-κB signaling pathways (Xianyuan et al, 2019). Similar therapeutic effects are also found in other studies with herbal medicines (Nie et al, 2014;Wan et al, 2014;Zhao et al, 2016). Targeting Smad3-dependent non-coding RNAs could be another therapeutic approach to treat renal fibrosis and inflammation (Figure 4c).…”
Section: Treatment Of Ckd By Targeting Downstream Tgf-β/smad Signalinsupporting
confidence: 62%
“…TS formula is produced from six types of traditional Chinese medicine, namely Astragalus, Radix puerariae, Lucid ganoderma, Ligustrum lucidum, Rheum officinale and Salvia miltiorrhiza. Astragalus and Radix puerariae (15). Astragalus is beneficial for supplementing Qi and strengthening the immune system (36).…”
Section: Discussionmentioning
confidence: 99%
“…Chinese medicinal treatment applies multi-channel and multi-target activities to achieve positive and effective therapeutic effects, thus the application of traditional Chinese medicine has great potential in the prevention of DN. According to the traditional Chinese medicine theory of Professor Kefu Chai, it is believed that the basic pathogenesis of early-and medium-stage DN is the deficiency of both Qi and Yin, which results in blood stasis (15). Previous results have indicated that a Chinese herbal compound prescription, Tangshen (TS) formula, has demonstrated good clinical efficacy in managing early-stage DN, as it is believed in traditional Chinese medicine that it supplements Qi, nourishes Yin, improves blood flow and removes obstructions in the blood vessels (16).…”
Section: Introductionmentioning
confidence: 99%
“…In modern times, Many patients have turned to Chinese herbal medicine for treatment as a complementary and basic combinationdrug therapy for kidney disease in China due to its fewer adverse reactions and more effective interventions. Currently, a research from Taiwan has demonstrated that patients with CKD who used CHM had a significantly reduced ESRD risk (60%) [46].Relevant clinical observations have shown that TSF appears to prevent further development and deterioration of the disease, which includes the reduction of urinary albumin and the normalization of glomerular filtration rate [47][48][49][50].Potential mechanisms have been proved that herbal medicine could regulate oxidative stress which is well recognized that oxidative stress plays a major role in worsening of DKD [50][51][52].However, there is less clinical research on delaying the progression of DKD, especially in the early stage as only period of reversing kidney lesion. This work has the potential function to delay the development of DKD.…”
Section: Discussionmentioning
confidence: 99%